ANALISIS EFEKTIVITAS PENERAPAN STANDAR OPERASIONAL PROSEDUR (SOP) PADA RESTORAN SQUARE DI NOVOTEL MANADO GOLF RESORT & CONVENTION CENTER - Mewengkang, Meilan; Lumare, Mercy; Tenda, Mirjam P. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Service delivery at Square Restaurant of Novotel Manado Golf Resort & Convention Center still revealed a gap between the established Standard Operating Procedure (SOP) and its day-to-day execution, particularly across the stages of welcoming the guest, order taking, anticipating guests needs, cashier billing, and farewell the guest. This study was designed to assess how effectively the SOP is implemented within the restaurant service operation. A quantitative approach combining descriptive and associative methods was applied, involving all fourteen permanent employees as respondents through total sampling. Data were obtained from questionnaires, direct observation, documentation, and a literature review, then processed using validity and reliability testing, a normality test, simple linear regression, the t-test, and the coefficient of determination with IBM SPSS Statistics 30. The analysis generated the regression model Y = 19.081 + 0.571X, while the t-test produced a calculated value of 4.898, exceeding the critical value of 2.179 at a significance level of 0.000. The coefficient of determination reached 0.667, indicating that SOP implementation explained 66.7% of service effectiveness, with the remaining 33.3% attributable to factors outside this study. The results confirm that a consistent and disciplined application of the SOP meaningfully strengthens service effectiveness, even though several stages, especially repeat order, table check, and farewell the guest, still call for greater consistency.